A Distinct Arabidopsis Latent Virus 1 Isolate Was Found in Wild Brassica hirta Plants and Bees, Suggesting the Potential Involvement of Pollinators in Virus Spread - Victoria Reingold; Avi Eliyahu; Neta Luria; Diana Leibman; Noa Sela; Oded Lachman; Elisheva Smith; Yael Mandelik; Asaf Sadeh; Aviv Dombrovsky (Plants, 2024)
During our search for aphid-pathogenic viruses, a comovirus was isolated from wild asymptomatic Brassica hirta (white mustard) plants harboring a dense population of Brevicoryne brassicae aphids. The transmission-electron-microscopy visualization of purified virions revealed icosahedral particles. The virus was mechanically transmitted to plants belonging to Brassicaceae, Solanaceae, Amaranthaceae, and Fabaceae families, showing unique ringspot symptoms only on B. rapa var. perviridis plants. The complete viral genome, comprised of two RNA segments, was sequenced. RNA1 and RNA2 contained 5921 and 3457 nucleotides, respectively, excluding the 3′ terminal poly-adenylated tails. RNA1 and RNA2 each had one open-reading frame encoding a polyprotein of 1850 and 1050 amino acids, respectively. The deduced amino acids at the Pro-Pol region, delineated between a conserved CG motif of 3C-like proteinase and a GDD motif of RNA-dependent RNA polymerase, shared a 96.5% and 90% identity with the newly identified Apis mellifera-associated comovirus and Arabidopsis latent virus 1 (ArLV1), respectively. Because ArLV1 was identified early in 2018, the B. hirta comovirus was designated as ArLV1-IL-Bh. A high-throughput-sequencing-analyses of the extracted RNA from managed honeybees and three abundant wild bee genera, mining bees, long-horned bees, and masked bees, sampled while co-foraging in a Mediterranean ecosystem, allowed the assembly of ArLV1-IL-Bh, suggesting pollinators’ involvement in comovirus spread in weeds.